Functions of the orbital prefrontal cortex and hippocampus in goal-directed behavior and memory - Mariano, T (2006)
Ailments such as Alzheimer’s disease (AD) and frontotemporal dementia (FTD) are devastating conditions linked to deficits in the human prefrontal cortex, with some apparent localization to the orbital prefrontal cortex (OPFC). Prior work suggests structural and functional homology in the prefrontal cortex across species but many discrepancies remain. The primary aim of this project was thus to characterize the behavioral similarities and differences of the OPFC. Cytotoxic ablations of either the OPFC or hippocampus (HPC) of rodents permitted investigation of dissociations of function between the two structures. These experiments demonstrated that the HPC was required for a variety of anxiety behaviors, whereas the OPFC was implicated in only a hyponeophagia test, perhaps suggesting a more complex modulatory role for that structure. The OPFC was relatively uninvolved in spatial learning and memory or in reversal learning, contrary to large deficits observed in all aspects of spatial behavior following HPC lesions. OPFC lesions resulted in decreased levels of spontaneous locomotor activity; however, the age of the rodents at the time of this test may have been a confounding factor. A test of goal-directed behavior—-reinforcer devaluation—-was unsuccessful due to deficiencies in the testing paradigm. Finally, a technical proof-of-concept demonstrated successful use of intra-orbital 5,7-dihydroxytryptamine (5,7-DHT) to produce selective serotonin (5-HT) depletions in the OPFC for future studies. The results of this work will aid in the development of better therapies for AD and FTD.